2021
DOI: 10.1002/cnma.202100119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viscosity on Microswimmers: A Comparative Study

Abstract: Although many biological fluids like blood and mucus exhibit high viscosities, there are still many open questions concerning the swimming behavior of microswimmers in highly viscous media, limiting research to idealized laboratory conditions instead of application‐oriented scenarios. Here, we analyze the effect of viscosity on the swimming speed and motion pattern of four kinds of microswimmers of different sizes which move by contrasting propulsion mechanisms: two biological swimmers (bovine sperm cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…We speculate that this observation was probably related to the fact that the disassembly of the P3 L brushes was either inefficient and/or resulted in an increased local viscosity that might have impaired the locomotion of these motors (Movie S4, Supporting Information). [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that this observation was probably related to the fact that the disassembly of the P3 L brushes was either inefficient and/or resulted in an increased local viscosity that might have impaired the locomotion of these motors (Movie S4, Supporting Information). [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…13 However, this elegant approach does not give realistic estimates for photoactive systems. Measurements of the displaced water volume by gas evolution can measure the specifications of colloids, 27 but have not been used on photoactive systems. To achieve a precise measurement of the O 2 generation on a defined amount of particles, we developed a Janus Au@TiO 2 colloidal monolayer with well-known dimensions (see SEM image Fig.…”
Section: Motion Mechanismsmentioning
confidence: 99%
“…It was found that micrometer-sized Janus particles and tubular swimmers experience drag-related speed reductions when swimming in viscous media. [64,74,75] An interesting effect, that is frequently overlooked in physical considerations, is the influence of polymers on the catalysts that create flows for propulsion, which has no direct counterpart in biological systems, but the toxicity that the polymer molecules might have on cells shows certain similarities. [64]…”
Section: Swimming In Highly Viscous Environmentsmentioning
confidence: 99%
“…[57][58][59][60][61][62][63] A first attempt to interpret this behavior by Berg and Turner ascribed this to the gel-like behavior of the network formed by the polymer chains. [58] However, depending on the specific polymer, its behaviors, and effects on the biological entities, this behavior can be weak [64] or even absent as experienced for specific smooth-swimming E. coli. [60,63] A recent work looked in very much detail at the interactions between E. coli and colloidal obstacles, concluding that it might actually be path-straightening, instead of polymer dynamics that cause the speed enhancement.…”
Section: Swimming In Highly Viscous Environmentsmentioning
confidence: 99%